SYNTHESIS OF HYDROGEL SUPERABSORBEN BASED ON ACRYLAMID AND ACRYLIC ACID IN ATMOSPHERE CONDITION - Agus Salim; Suwardi Suwardi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2009)
The aim of this research is to synthesis poly(acrylic-acrylamide) at atmosphere condition and know absorbency or swelling degree of polymer that produced in water or urine. The synthesis was done through the mixing of 2 mL acrylic acid with potassium hidroxide solution so that potasium acrylic salt formed, then this salt solution was mixed with a mixtures of methylene bis-acrylamide (MBA), potassium persulphate and sodium metabisulphite (SMBS) solutions. The gels were formed and then dried at 70 oC during 18 hours for obtaining constant weight. The result of synthesis was white hydrogel analysed using FTIR spectrometry method and measured its absorbency or swelling degree in water or urine. Based on the result of its water absorbency was found that the synthesed polymer using 0.02 g MBA and 0.014 g SMBS might absorbed 184.76 g water per gram polymer